FRI0200 REVIEW OF HYDROXYCHLOROQUINE USE AND DEVELOPMENT OF A REGIONAL STRATEGY TO MINIMISE RETINAL TOXICITY. (June 2019) - Laverty, Ursula; Reid, Gerard; Silvestri, Julie; Pendleton, Adrian
Abstract : Background: Guidelines from the Royal College of Opthalmologists in February 2018 were developed for retinal screening for patients on hydroxychloroquine, as recent evidence suggests the risk of retinal toxicity is higher than previously reported. The prevalence of retinal toxicity in long term use appears to be 7.5% and depending on dose and duration of therapy can increase to 20-50% after 20 years of therapy. Risk is increased for patients taking more than 5mg per kg per day of hydroxychloroquine, patients on Tamoxifen and those with renal impairment. The guidelines recommend the use of a standardised referral proforma to help identify patients who are high risk. Objectives: 1. Audit of Hydroxychloroquine use and retinal screening in the Belfast Health and Social Care Trust (BHSCT) 2. Develop a regional referral proforma and screening service for retinal toxicity Methods: Patients who were treated with hydroxychloroquine, under the care of a consultant rheumatologist were identified on the database. A proforma was used to aid data collection and patients' electronic records were reviewed. We audited the use of hydroxychloroquine and retinal screening against current Royal College of Ophthalmology (RCO) guidelines. We designed a standardised referral proforma and regional screening strategy in conjunction with ophthalmology colleagues. Results: There were 151 patients identified on hydroxychloroquine on the database. 40 of these patients had stopped hydroxychloroquine, 2 of which had retinal toxicity. Therefore the rate of retinal toxicity in this sample was 1.3% (2/151). There were 111 patients who remained on hydroxychloroquine treatment with a female: male ratio of 9:1. Age range was from 22 to 84, with a mean age of 55. There were 44% of patients on hydroxychloroquine for rheumatoid arthritis, 25% had systemic lupus erythematosus, 8% had Sjogrens syndrome, 6% had pallindromic rheumatoid arthritis and 13% had other connective tissue diseases. The majority (79%) of patients were on 200mg hydroxychloroquine daily and 19% were on 400mg daily. 6% of patients had an eGFR<60. No patients were on tamoxifen. 73% of patients were on hydroxychloroquine treatment for over 5 years. Retinal screening was overdue in 64% of patients. Conclusion: In this sample, only 1.3% of patients had evidence of retinal toxicity, although 64% of patients were overdue retinal screening. We developed a referral proforma and a regional screening strategy in line with RCO guidelines. In order to meet the RCO guidelines, we recognise the need for substantial investment in regional ophthalmology services. References: [1] Royal College of Ophthalmologists. (2018) Clinical Guidelines. Hydroxychloroquine and Chloroquine Retinopathy:Recommendations on Screening. Disclosure of Interests: None declared